2014
DOI: 10.5352/jls.2014.24.5.498
|View full text |Cite
|
Sign up to set email alerts
|

Screening of Hyaluronidase Inhibitor in Korean Medicinal Plants

Abstract: Mammalian hyaluronidases (HAase, EC 3.2.1.35) are a family of enzymes that hydrolyse N-acetyl-Dglucosamine (1-4) glycosidic bonds in hyaluronic acid, which is found in skin, cartilage, and the vitreous body. Although HAase is generally present in an inactive form within subcellular lysosomes, it is released in an active form in some types of inflammation and tissue injuries, thereby contributing to the inflammatory response. The HAase inhibitory activity of 500 methanolic extracts of 500 species from medicinal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 22 publications
0
6
1
Order By: Relevance
“…Curcuma aromatica exhibited the best hyaluronidase inhibition activity (95%). Large-scale studies were performed by Hwang et al [ 38 ], in which the inhibitory activity of 500 methanolic extracts of 500 species from medicinal plants was analyzed. Only three MeOH extracts inhibited more than 50% of Hyal activity at a concentration of 2 mg/mL.…”
Section: Resultsmentioning
confidence: 99%
“…Curcuma aromatica exhibited the best hyaluronidase inhibition activity (95%). Large-scale studies were performed by Hwang et al [ 38 ], in which the inhibitory activity of 500 methanolic extracts of 500 species from medicinal plants was analyzed. Only three MeOH extracts inhibited more than 50% of Hyal activity at a concentration of 2 mg/mL.…”
Section: Resultsmentioning
confidence: 99%
“…Hwang et al [8] Kwon et al [12] reported that roots of A. japonica showed relatively high antioxidant activities. In this study, DPPH values of A. japonica were slightly high (Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…HAase assay was validated by demonstrating that pure tannic acid (0.07 mg/ml Sigma-Aldrich Co., England) as a positive control, a known HAase inhibitor [7], gives 76-80% enzyme inhibition [8]. All experiments were done in triplicate.…”
Section: Hyaluronidase Inhibition Assaymentioning
confidence: 99%
“…A major screening study on 500 Korean Medicinal plants as HAase inhibitors identified the stem extract of three species possessing relatively higher anti-HAase activity include plant specied Styrax japonica (57.28%), Deutzia coreana (53.50%), and Osmanthus insularis (53.19%). The study further explores that the HAase inhibition could be due to presence of multifunctional compounds and may be effective in preventing allergic reactions and inflammation [81].…”
Section: Anti-hyaluronidase Medicinal Plant Extractsmentioning
confidence: 99%